2002
DOI: 10.1109/tip.2002.804260
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of perceptually important colors and similarity measurement for image matching, retrieval and analysis

Abstract: Color descriptors are among the most important features used in image analysis and retrieval. Due to its compact representation and low complexity, direct histogram comparison is a commonly used technique for measuring the color similarity. However, it has many serious drawbacks, including a high degree of dependency on color codebook design, sensitivity to quantization boundaries, and inefficiency in representing images with few dominant colors. In this paper, we present a new algorithm for color matching tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 15 publications
0
64
0
Order By: Relevance
“…The dataset were tested for video retrieval using sum of squared pixel difference (SSD) measure [19] between videos' keyframes, leaving any temporal information without utilization and relying on annotations which is neither accurate (due to dependency on human element) nor always available. Color proved to be a powerful feature regarding image retrieval [22,23] and video retrieval [24,25], as it's strongly related to semantic similarity [26,27]. Color by nature is invariant to partial occlusion, cropping, translation or affine transformations such as scaling, rotation, shear or reflection [24].…”
Section: Typesmentioning
confidence: 99%
See 3 more Smart Citations
“…The dataset were tested for video retrieval using sum of squared pixel difference (SSD) measure [19] between videos' keyframes, leaving any temporal information without utilization and relying on annotations which is neither accurate (due to dependency on human element) nor always available. Color proved to be a powerful feature regarding image retrieval [22,23] and video retrieval [24,25], as it's strongly related to semantic similarity [26,27]. Color by nature is invariant to partial occlusion, cropping, translation or affine transformations such as scaling, rotation, shear or reflection [24].…”
Section: Typesmentioning
confidence: 99%
“…Color by nature is invariant to partial occlusion, cropping, translation or affine transformations such as scaling, rotation, shear or reflection [24]. Color feature is very powerful and could act as a building block for efficient video matching techniques, especially in absence of any semantic cues [26]. Furthermore, humans tend to see scenes as a set of dominant colors [26,28] as it was found that a small number of colors are sufficient to describe any region instead of a full color space [29].…”
Section: Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…. Finally, a perceptual metric (OCCD) [12] is used to determine the similarity of two color feature vectors.…”
Section: Segmentation Algorithm Overviewmentioning
confidence: 99%